2018
DOI: 10.1021/acs.nanolett.8b03235
|View full text |Cite
|
Sign up to set email alerts
|

Scaling Behavior of Ionic Transport in Membrane Nanochannels

Abstract: Ionic conductance in membrane channels exhibits a power-law dependence on electrolyte concentration ( G ∼ c). The many scaling exponents, α, reported in the literature usually require detailed interpretations concerning each particular system under study. Here, we critically evaluate the predictive power of scaling exponents by analyzing conductance measurements in four biological channels with contrasting architectures. We show that scaling behavior depends on several interconnected effects whose contribution… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 62 publications
1
20
0
Order By: Relevance
“…The conventional explanation of AMFE points to the correlated movement of ions in a single file fashion [ 19 ] characteristic of very narrow channels like gramicidin A [ 32 ]. However, E channel unitary conductance is similar to another multiionic proteolipidic pore, Alamethicin, in its lowest conductance state [ 9 , [33] , [34] , [35] ], which implies that it allows the transport of fully hydrated ions, water molecules and small molecules [ 22 ]. Since single-file transport of dehydrated ions seems highly improbable in multi-ionic pores such as synthetic nanopores where AMFE has already been reported [ 25 ], it has been suggested that AMFE may appear also because of localized, ion-specific binding within the pore [ 25 ].…”
Section: Resultsmentioning
confidence: 99%
“…The conventional explanation of AMFE points to the correlated movement of ions in a single file fashion [ 19 ] characteristic of very narrow channels like gramicidin A [ 32 ]. However, E channel unitary conductance is similar to another multiionic proteolipidic pore, Alamethicin, in its lowest conductance state [ 9 , [33] , [34] , [35] ], which implies that it allows the transport of fully hydrated ions, water molecules and small molecules [ 22 ]. Since single-file transport of dehydrated ions seems highly improbable in multi-ionic pores such as synthetic nanopores where AMFE has already been reported [ 25 ], it has been suggested that AMFE may appear also because of localized, ion-specific binding within the pore [ 25 ].…”
Section: Resultsmentioning
confidence: 99%
“…To recapitulate, our results demonstrate the importance of lipid membrane composition in the mechanism of voltage-induced gating in large bacterial β-barrel channels. This adds to the number of central channel properties such as open channel current, selectivity, and interaction with partners that depend crucially on membrane composition [12,43,44,45,46,47,48,49]. In particular, we show unambiguously that lipid headgroup charge is an important modulator of OmpF gating, but it is not the only factor.…”
Section: Discussionmentioning
confidence: 60%
“…wileyonlinelibrary.com/journal/exploration  of  https://doi.org/10.1002/EXP.20210101 F I G U R E  Representative membrane structures for rational ion transport management, including nanochannel-structured membranes with single-dimensional nanochannels (i.e., 1D, 2D, and 3D) and mixed-dimensional nanochannels (i.e., 1D/1D, 1D/2D, 1D/3D, 2D/2D, 2D/3D, and 3D/3D), ultrathin membranes, and sandwich-like membranes, and their broad applications in the fields of ion separation, water purification, energy storage and conversion, sensors, and bioelectronics biological ion channel proteins [14][15][16][17][18][19][20][21] or artificial components with channels [22,23] in phospholipid bilayers. Reconstructed EcClC proteins embedded in lipid bilayers can function as H + and Cl − pumps with improved and controllable transport properties because of the superimposing or counterimposing gradients of H + and Cl − ions.…”
Section: Introductionmentioning
confidence: 99%